Filipino family's caregiving capacity for selected schizophrenics in a government tertiary hospital - Espana, Lisette Matutina (1999)
aThe last decade has witnessed a renewed interest in the family of the individualwith schizophrenia. Various studies have shown that a family plays an important role in the treatment of the schizophrenic(Handley, 1986; Henderson, 1988; Baker, 1989; Goldman Quinn, 1998; Koenigsberg Handley, 1986). Literature also proves that certain factors like culture, social status, ethnicity and attitude play central role in shaping the family's experiences of caregiving.In this light, this study was conducted to(1) obtain a profile of family caregivers of schizophrenic in terms of demographic variables, caregiving capacity and attitudes towards schizophrenia; (2) obtain a profile of schizophrenicscared by family caregivers; (3) determine the relationship between demographic variables and the caregiving capacity of family caregivers of schizophrenics; (4) determine the relationship between attitude of caregivers towards schizophrenics and caregiving capacity; (5) see if certain illnessand treatment - related variables affect the caregiving capacity of caregivers of schizophrenics; and (6) identify problems encountered in caregiving of schizophrenics.The study utilized a descriptive correlational research design. The study was conducted at the Philippine General Hospital Ward 7 - Psychiatry Ward. A total of fifty family caregivers of schizophrenics participated in the study. Caregivers who consented participate in the study were given questionnaires and interviewedby the investigator.The result of the study showed that the caregiving capacity scores of family caregivers ranged from 87 to 150. The scores are relatively high and are widely distributedhaving a mean score of 132. From the overall ranking, six among the top ten caregiving tasks are physical tasks. The caregivers are more used to fulfilling physiologic needs because these are the basic things done for any human being with or without illness. Among the physical tasks, the top 4 are tasks usually learned at home. Regarding psychosocial tasks, the results revealed that the item on show of concern ranked highest as this is a cultural expectation among families that they would protect and provide security to their members. Assistance in decision-making, identification of good traits and guidance in self-expression also ranked high at no. 2,3 4 respectively. For illness-related tasks, the data showed that the item on ensuring intake of medications is the highest.
The caregivers are not knowledgeable about the approaches towards the mentally ill like consistency (rank no. 6) and psychotherapy (rank no. 9 10). The mean scores of caregiving tasks addressing patients' symptoms like hallucination and anxiousness are the lowest.Furthermore, the caregivers reported their difficulties and problems in caring for their mentally ill relative. The problem areas can be categorized into: caregiver problems and patient problems. Under caregiver problems are the following: inability to understand patients' behavior (12), "don't know" how to manage violent behavior (6) and financial loss (4). For patient problems include non-compliance with medications (14), recurrence of symptoms (6) and side effects of medications (6).Meanwhile, the attitudinal scores of the 50 caregivers ranged from 112-152. The scores are also relatively high having a mean score of 134.52. For the parameters on accessibility, the findings show that the items on spending time to discuss patient concerns and attend to immediate needs ranked no.1 and 2 respectively, not only for this portion but overall for attitude. For the parameter on acceptance, most of the caregivers accept their responsibility as caregiver (rank no. 1). The caregivers are also aware of the importance of family support for the schizoprenic as its ranking is no. 2. What is significant in the result is the item on acceptance of schizophrenia as a common psychiatric illness ranked very low for caregivers. It seems to show that caregivers are somewhat ignorant about schizophrenia. For the parameter on understanding, te data revealed that the item on coordinating with the health team is the for caregivers. Caregivers also believed that medication is important for the treatment of the mentally ill (rank no. 3). It is also striking to note that families do not seem convinced that exacerbation of the disease can be prevented as this ranked no. 21 overall for attitude. The item on isolating agitated patients ranked lowest. For the parameter on hope, most of the caregivers are hopeful that medications can improve their patients' condition (rank no. 1). Items on expectations about getting well and continuing to care also ranked high at no. 2 and 3 respectively. It is sad to note that the item on family getting closer because of patients' illness is the lowest for caregivers (rank no.8). Lastly, for attitude parameter, all items on empathy ranked low overall for caregivers. Caregivers are likely to show sympathy than emphaty towards an ill relative.To determine the significant relationship between the following demographic variables of age, sex, educational attainment, occupation, relationship to the patient and availability of care relievers with the caregiving capacity of family caregivers of schizophrenics, Pearson Product Moment Correlation, T-test and ANOVA were used with significance level set at .05. Results showed that the demographic variables mentioned are not significantly related with the caregiving capacity of family caregivers. To determine the significant relationship between attitude and caregiving capacity of family caregivers of schizophrenics, Pearson Product Moment Correlation was utilized. The results revealed that attitude has a positive relationship with the caregiving capacity of family caregivers of schizophrenics. These two variables are directly correlated meaning if the attitude score is high, the caregiving capacity score also tend to be high. This implies the more caring the attitude for the caregiver, the greater is the capability to meet the needs of their mentally ill relative.
To determine the significant relationship between the following illness and treatment - related variables of age at onset of illness, length of illness, number of hospitalization and reason for admission with the caregiving capacity of family caregivers of schizophrenics, Pearson Product Moment Correlation and ANOVA were used. The data showed that there is no significant relationship between the variables. Although the study was able to point out a significant relationship between attitude and caregiving capacity of family caregivers of schizophrenics, it should be emphasized that one's caregiving abilities do not depend entirely on one's attitude towards mental illness.It is hoped that data from this study will guide the other researchers and psychiatric nurse in planning their nursing interventions and programs for schizophrenics and their families. Recommendations are also directed towards increasing competence of nurses in family interventions and to explore avenues for in-depth training of nurses as family therapist.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Schizophrenics; Caregivers